Preoperative C-Reactive Protein–Albumin–Lymphocyte Index and Related Clinical Factors Associated With Postoperative Complications Following Cholecystectomy in Acute Cholecystitis: A Retrospective Study - Huanhuan Chen; Yefeng Yao; Xiangyu Zhang (Annali Italiani di Chirurgia, 2026)
AIM: Laparoscopic cholecystectomy (LC) is the primary treatment for acute cholecystitis (AC), although various postoperative complications may still occur. Inflammatory composite indices have gained increasing attention in surgical risk assessment; among them, the C-reactive protein–albumin–lymphocyte (CALLY) index integrates systemic inflammation, immune function, and nutritional status. This study aimed to investigate the association between preoperative CALLY index and postoperative complications in patients with AC undergoing cholecystectomy.METHODS: This retrospective cohort study included 330 patients with AC who underwent cholecystectomy at the Department of General Surgery, Sir Run Run Shaw Hospital, Zhejiang University School of Medicine, between January 2015 and December 2024. Patients were categorized according to the occurrence of postoperative complications. Clinical characteristics, perioperative variables, and preoperative laboratory markers were collected. The CALLY index was calculated using C-reactive protein (CRP), albumin, and lymphocyte count. Between-group comparisons, Spearman correlation analysis, receiver operating characteristic (ROC) curve analysis, and logistic regression analyses were performed to examine the associations of the CALLY index and related clinical factors with postoperative complications and to evaluate their discriminative ability.RESULTS: Among the 330 patients, 83 (25.2%) experienced postoperative complications. Patients with complications were older and had higher rates of diabetes, gallbladder wall thickness ≥5 mm, and a history of previous cholecystitis (all p < 0.001). Preoperative CRP levels were elevated, whereas albumin, lymphocyte counts, and CALLY index values were lower in the complication group (all p < 0.001). ROC analysis demonstrated that the CALLY index had favorable predictive ability (area under the curve [AUC] = 0.720). Multivariate analysis identified age, diabetes, gallbladder wall thickness, history of cholecystitis, American Society of Anesthesiologists Physical Status (ASA-PS) classification, the 2018 Tokyo Guidelines (TG18) grade, and CALLY index as independent predictors of postoperative complications (all p < 0.05).CONCLUSIONS: Preoperative CALLY index is associated with the occurrence of postoperative complications in patients with AC undergoing cholecystectomy. CALLY index may serve as a supplementary preoperative marker for identifying patients with a higher risk of postoperative complications. However, further prospective multicenter studies are needed to validate its clinical applicability.